SYNTHESIS AND CHARACTERIZATION OF CATALYTIC ALPHA ALUMINA SUPPORTED SYSTEMS Ni, Ni-W Y Ni-Cu-W BY DRX, TPR Y SEM ABSTRACT - Delmas R., D. L. (2009)
The objective of the present investigation is to show the synthesis of the catalytic systems Ni, Ni-W and Ni-Cu-W supported on alpha alumina by impregnation method, the characterization of the catalytic systems by XPS, TPR and SEM. The results of the XRD analysis show that the metallic components are as NiO, CuO and W03 oxides. The TPR results show the existence of the synergic effect in the bimetallic and tree-metallic alpha alumina supported systems. Finally, the results of the SEM show the micrography and the surface composition of the catalysts: Ni-W/α-Al3 y Ni-Cu-W/α-Al2, respectively.